PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA, DISIPLIN KERJA DAN KINERJA KARYAWAN PT. KERETA API INDONESIA (PERSERO) DAOP IX JEMBER - Primandaru, Dinarizka Leksi; Tobing, Diana Sulianti; Prihatini, Dewi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
This research aims to analyze and empirically prove the direct influence of work motivation and work environment on the employee performance, and the indirect influence of work motivation and work environment on the employee performance through work satisfaction and work discipline in PT Kereta Api Indonesia (Persero) Daop IX Jember. This is an explanatory research applying the proportionate sampling method. The population was all 163 employees of PT Kereta Api Indonesia (Persero) Daop IX Jember. The sample of every sub-population was determined by dividing the sub-population with the number of population member multiplied by the member size of the sample that resulting in the total sample of 118 respondents. Data were collected from the questionnaire distribution and analyzed by Structural Equation Modelling (SEM) using IBM SPSS AMOS 20 software. Results of the study proved that all hypothesis were accepted meaning that motivation influences performance directly and indirectly through work satisfaction, and work environment influences performance directly and indirectly through work discipline. Keywords: Motivation, Work Environment, Satisfaction, Discipline, Performance